Performance and Egg Qualities of Isa-Brown Layers Fed Different Quantities of Feed at Varying Feeding Frequencies - Muyiwa Adegbenro; Abiodun S. Ajidara; Stephen G. Modupe; Gbenga E. Onibi (Turkish Journal of Agriculture: Food Science and Technology)
Most poultry farmers in Nigeria feed their laying birds twice a day with one bag of 25 kg to 200 layers which translate to 125g/bird/day, while very few feed once or thrice a day and there has been little or no documentation on how many times laying hens should be fed in a day to optimize profit. Thus, this study was designed to investigate the performance and egg qualities of Isa-Brown layers fed different quantities of feed at varying feeding frequencies. Three hundred and sixty (360) 16-weeks in-lay Isa-Brown layers were used in this trial. The treatment consisted of 95g, 105g, 115g, and 125g of feed per day at varying frequencies of once, twice and thrice per day. The birds were housed in California type cages, 3 birds per cage unit, 5 cage units per replicate, and 6 replicates per treatment. A completely randomized experimental design with a 4x3 factorial was adopted. Results at the end of the trial showed that bird fed 115g of feed twice per day had the highest percentage hen-day production (85.24%), highest egg mass (56.69g) and best feed conversion ratio (1.96) while lowest percentage hen-day production (62.02%) and lowest egg mass (39.22g) were observed in hen fed 95g of feed thrice per day and worst feed conversion ratio (2.50) was recorded in bird fed 125g of feed thrice per day. The bird fed 115g twice per day had the highest net profit (N637.63) while the lowest net profit (N199.33) was recorded in bird fed 125g thrice per day. It could be concluded that for optimum laying performance and to save time and labour expended in feeding birds thrice per day, feeding laying Isa-Brown birds the required feed quantity (115g) twice per day would be most economical.